PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KINERJA LINGKUNGAN, DAN STRUKTUR CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Haryati, Rima; Nur Rahardjo, Shiddiq (Diponegoro Journal of Accounting, 2013)
The objectives of this research is to examine the impact of Corporate Social Responsibility, environment and corporate governance structure (public ownership and size of audit commitee) towards financial firm performance. Sample of this research is companies listed on the Indonesia Stock Exchangeand participated in PROPER in 2008 to 2010, which are 63 firms. Purposive sampling was used as sampling method. Data analysis method used was multiple regression analysis. Result of this research indicate that CSR disclosure and public ownership significantly effect on firm performance. However, environment performance and size of audit commitee hasn’t effect towards firm performance.